2002
DOI: 10.1097/00005110-200205000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Job Satisfaction, Organizational Commitment, and Career Intent

Abstract: Findings of this investigation suggest the organizational environment, educational preparation, and personal characteristics of currently employed registered nurses affect their current job satisfaction, organizational commitment, and plans for continuing as a nurse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
233
4
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(263 citation statements)
references
References 46 publications
15
233
4
7
Order By: Relevance
“…This finding is in agreement with study results which showed a close positive correlation between job satisfaction and organizational commitment. [80] In addition to job satisfaction, safety issues such as investigating the relationship between working hours and patient safety (medication errors), or staff injury by observing the staff while administering medications at flexible times is an identified gap which should be filled by scientific research. However, it is important to notice that fatigue and sleepiness could be risk factors leading to medication errors, thus examining the relationship of these factors is significant also in terms of the quality of care given.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with study results which showed a close positive correlation between job satisfaction and organizational commitment. [80] In addition to job satisfaction, safety issues such as investigating the relationship between working hours and patient safety (medication errors), or staff injury by observing the staff while administering medications at flexible times is an identified gap which should be filled by scientific research. However, it is important to notice that fatigue and sleepiness could be risk factors leading to medication errors, thus examining the relationship of these factors is significant also in terms of the quality of care given.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding factors related to nurse turnover, age, job title, nursing experience, community satisfaction 2) , marital status 2,11,12) , living together with a child 11) , moving 12) , salary [11][12][13] , burnout 10,23) , job satisfaction 2,4,13,32) , hardness 4) , interpersonal relationships with doctors, senior nursing staff and patients 12,13) , organization commitment 32) , and lumbar pain 33) have been reported. These factors differed from those affecting the rapid turnover of novice nurses in university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…To increase retention, organizations should explore strategies to maintain and improve working conditions (including shiftwork and psychosocial factors) and sustain healthcare workers' health and work ability as they age. Ageing is typically associated with decreased physical health, while the relationship between ageing and outcomes such as job satisfaction, absenteeism and injuries is more controversial, with studies indicating that being older may actually protect employees (Beatty and Burroughs, 1999;Ingersoll et al, 2002;Taimela et al, 2007).…”
Section: Ageing and Shiftworkmentioning
confidence: 99%